1984
DOI: 10.1104/pp.74.3.510
|View full text |Cite
|
Sign up to set email alerts
|

Invertases of Lilium Pollen

Abstract: ITwo different forms of invertase are found in pollen of lily (Lilium anratum). One form is cytoplasmic (Invertase 1) and the other is bound to the pollen wall (Invertase 2). Invertase 1 has been partilly purifed and is a glycoprotein (apparent molecular weight, 450 kilodaltons) with a K, of 0.65 millimolar for sucrose. The two invertases differ in pH optimum and thermal stability. Invertases of lily pollen are ,@-fructofuranosidases which can hydrolyze sucrose but not melizitose. The mature pollen grains have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…This result is consistent with studies of lily pollen invertases where the involvement of a sulfhydryl group in the enzyme's catalytic site has been suggested (23). However, 100 Mm DTNB and 100 gM NEM, reagents known to react with sulfhydryl groups, failed to inhibit the wheat invertase activity to any measurable extent.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…This result is consistent with studies of lily pollen invertases where the involvement of a sulfhydryl group in the enzyme's catalytic site has been suggested (23). However, 100 Mm DTNB and 100 gM NEM, reagents known to react with sulfhydryl groups, failed to inhibit the wheat invertase activity to any measurable extent.…”
Section: Resultssupporting
confidence: 81%
“…The purified enzyme is probably a glycoprotein based on its ability to bind to the lectin Con-A. This is consistent with other studies (4,18,23) where it has been shown that invertase is a glycoprotein. The precise role of the carbohydrate moiety of the enzyme is not well understood since it is not necessary for enzymic activity or stability (4).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…INV activity was also 62 and 73% lower at day 2 and 4 of storage in HT samples. Last fact could be due to the sensitivity of INV to stress produced by the high temperatures (Singh andKnox 1984, Cheikh andJones 1995). In the case of samples treated with 1-MCP, INV activity was similar to that of controls (Fig.…”
Section: Enzymatic Activitiesmentioning
confidence: 80%